Stepwise correlation of TP53 mutations from pancreaticobiliary maljunction to gallbladder carcinoma: a retrospective study - Satoshi Kawakami (BMC, 2021)
Abstract Background The genetic changes underlying carcinogenesis in patients with risk factors of gallbladder carcinoma (GBC) remains controversial, especially in patients with pancreaticobiliary maljunction (PBM). This study aimed to clarify the association between risk factors of GBC and genetic changes using next-generation sequencing (NGS). Methods We retrospectively analyzed resected tissues of 64 patients who were diagnosed with GBC (n = 26), PBM [with GBC (n = 8), without GBC (n = 20)], and chronic cholecystitis, used as a control group (n = 10). DNA was extracted from tumors and their surrounding tissues, which were precisely separated by laser-capture microdissection. Gene alterations of 50 cancer-related genes were detected by NGS and compared with clinical information, including PBM status. Results The most frequent gene alterations in GBC tissues occurred in TP53 (50%), followed by EGFR (20.6%), RB1 (17.6%), and ERBB2 (17.6%). Gene alterations that were targetable by molecular targeted drugs were detected in 20 cases (58.8%). Statistical analysis of gene alterations and risk factors revealed that TP53 alteration rate was higher in GBC patients with PBM than those without PBM (p = 0.038), and the TP53 mutation rates in the epithelium of control patients, epithelium of PBM patients without GBC, peritumoral mucosa of GBC patients with PBM, and tumor tissue of GBC patients with PBM were 10, 10, 38, and 75%, respectively (p <  0.01). Conclusions TP53 alteration more than KRAS mutation was revealed to underlie carcinogenesis in patients with PBM.